Cultural Networks and UNESCO: Fostering Heritage Preservation Betwixt Idealism and Participation. (May 2014) - Singh, J. P.
<x content-type="archive" xml:space="preserve">Abstract</x> Cultural issues are prominent in UNESCO and almost define the identity of the organization. Despite the various controversies, this essay will demonstrate that the most durable influence of UNESCO's contributions to cultural heritage is in mobilizing global cultural networks that inform the collective understandings and governance of this issue. The recognition that cultural heritage is linked to economic development provides added importance to cultural networks linked with UNESCO. Nevertheless, this essay also shows that cultural governance at UNESCO has favored top-down decision-making, which often marginalizes local communities immediately impacted by the links with tourism, economic development, and cultural heritage. The essay explores cases that may provide exemplars for participatory development, policy priorities, and UNESCO expertise.